Facile synthesis of copper doped ZnO nanorods for the efficient photo degradation of methylene blue and methyl orange. Issue 8 (1st June 2020) - Shah, Aqeel Ahmed; Bhatti, Muhammad Ali; Tahira, Aneela; Chandio, Ali Dad; Channa, Iftikhar A.; Sahito, Ali Ghulam; Chalangar, Ebrahim; Willander, Magnus; Nur, Omer; Ibupoto, Zafar Hussain
Abstract: In this study, zinc oxide (ZnO) nanorods are doped with copper by low temperature aqueous chemical growth method using different concentrations of copper 5 mg, 10 mg, 15 mg and 20 mg and labeled as sample 1, 2, 3 and 4 respectively. The morphology and phase purity of nanostructures was investigated by scanning electron microscopy, and powder X-ray diffraction techniques. The optical characterization was carried out through UV–Vis spectrophotometer. The band gap of coper doped ZnO has brought reduction at 250–600 nm and it indicates the fewer time for the recombination of electron and hole pairs, thus enhanced photo degradation efficiency is found. ZnO exhibits nanorods like shape even after the doping of copper. The photo degradation efficiency for the two chronic dyes such as methyl orange MO and methylene blue MB was found to be 57.5% and 60% respectively for a time of 180 mints. This study suggests that the copper impurity in ZnO can tailor its photocatalytic activity at considerable rate. The proposed photo catalysts are promising and can be used for the waste water treatment and other environmental applications.